2017
DOI: 10.1021/acs.biochem.7b00668
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-Induced Deamidation of Corneal Dystrophy-Related Transforming Growth Factor β-Induced Protein

Abstract: Mutations in the transforming growth factor β-induced protein (TGFBIp) cause phenotypically diverse corneal dystrophies, where protein aggregation in the cornea leads to severe visual impairment. Previous studies have shown a relationship between mutant-specific corneal dystrophy phenotypes and the thermodynamic stability of TGFBIp. Using liquid chromatography-tandem mass spectrometry and nuclear magnetic resonance (NMR), we investigated correlations between the structural integrity of disease-related mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…The double bands seen for the A546D and A546D/P551Q FAS1-4 domains (Fig. 2 A ) are, as shown previously (26), because of deamidations. The deamidations did not affect HtrA1 specificity and activity because both bands were degraded to the same extent.…”
Section: Resultssupporting
confidence: 87%
“…The double bands seen for the A546D and A546D/P551Q FAS1-4 domains (Fig. 2 A ) are, as shown previously (26), because of deamidations. The deamidations did not affect HtrA1 specificity and activity because both bands were degraded to the same extent.…”
Section: Resultssupporting
confidence: 87%
“…TGFβI encodes an ECM protein induced by TGFβ that interacts with collagen . Recent studies have shown that mutations in TGFβI in humans cause a condition known as granular corneal dystrophy, which is characterized by opaque deposits in the corneal stroma . Therefore, its upregulation in our data suggests that TGFβI may play a role in organizing collagen fibrils synthesized by the corneal endothelium and keratocytes during early development.…”
Section: Resultsmentioning
confidence: 61%
“…For FAS1-4, the same stability ranking was obtained using both urea and thermal denaturation, emphasizing the robustness of the conclusions. In addition, deamidation rates as a measure of structural integrity were similar for corresponding FAS1-4 and TGFBIp mutants (Nielsen et al, 2017).…”
Section: The Fas1-4 Domain Mimics Many Properties Of Full-length Tgfbip Making It An Excellent Model Systemmentioning
confidence: 79%